The Paradigm of Protecting the Reproductive Rights of Pregnant and Breastfeeding Female Prisoners in the Indonesian Correctional System - Azhar Anas Harahap; Nursariani Simatupang (Abdurrauf Law and Sharia, 2026)
This article examines the protection of the rights of pregnant and breastfeeding female prisoners within the Indonesian correctional system from the perspectives of law and reproductive justice. Although the rights of prisoners have been regulated in various statutory frameworks, previous studies have largely been dominated by descriptive-normative approaches and have not critically addressed the gap between the legal framework and its implementation, particularly in fulfilling women’s specific reproductive health needs within correctional settings. This study aims to critically analyze the fulfillment of the rights of pregnant and breastfeeding female prisoners and to evaluate the limitations of their implementation in correctional practice. This research employs a normative juridical method using statutory and conceptual approaches, supported by documentary studies of various legal sources and academic literature. The findings indicate that, normatively, the state has established an adequate legal protection framework. However, in practice, there is a significant gap between norms and implementation, as reflected in limited facilities, the lack of comprehensive reproductive health services, and the absence of an optimal gender-responsive approach within the correctional system. This study affirms that existing protections remain at the level of normative compliance and have not fully reflected substantive justice. Theoretically, it contributes by integrating a reproductive justice perspective into correctional law studies, while practically offering directions for policy reconstruction that are more responsive, inclusive, and aligned with global human rights standards. [Artikel ini mengkaji perlindungan hak narapidana perempuan hamil dan menyusui dalam sistem pemasyarakatan di Indonesia dalam perspektif hukum dan keadilan reproduktif. Meskipun pengaturan mengenai hak narapidana telah diatur dalam berbagai peraturan perundang-undangan, kajian sebelumnya masih didominasi oleh pendekatan deskriptif-normatif dan belum secara kritis mengkaji kesenjangan antara kerangka hukum dan implementasinya, khususnya dalam memenuhi kebutuhan spesifik perempuan terkait kesehatan reproduksi di lingkungan pemasyarakatan. Penelitian ini bertujuan untuk menganalisis secara kritis pemenuhan hak narapidana perempuan hamil dan menyusui serta mengevaluasi keterbatasan implementasinya dalam praktik pemasyarakatan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual, yang didukung oleh studi dokumenter terhadap berbagai sumber hukum dan literatur akademik. Hasil penelitian menunjukkan bahwa secara normatif negara telah menyediakan kerangka perlindungan hukum yang memadai. Namun, dalam praktiknya terdapat kesenjangan signifikan antara norma dan implementasi, yang ditandai oleh keterbatasan fasilitas, minimnya dukungan layanan kesehatan reproduktif yang komprehensif, serta belum optimalnya pendekatan berbasis kebutuhan gender dalam sistem pemasyarakatan. Penelitian ini menegaskan bahwa perlindungan yang ada masih berada pada tahap pemenuhan normatif dan belum sepenuhnya mencerminkan keadilan substantif. Secara teoretis, penelitian ini berkontribusi dengan mengintegrasikan perspektif keadilan reproduktif ke dalam kajian hukum pemasyarakatan, sementara secara praktis menawarkan arah rekonstruksi kebijakan yang lebih responsif, inklusif, dan selaras dengan standar hak asasi manusia global.]